Awareness of Unawareness: A Theory of Decision Making in the Face of Ignorance - Edi Karni; Marie-Louise Vierø (Queen's University, Department of Economics, 2014)
In the wake of growing awareness, decision makers anticipate that they might become aware of material possibilities and ideas that, in their current state of ignorance, are unimaginable. This anticipation manifests itself in their choice behavior. This paper models this awareness of unawareness and axiomatizes a probabilistic sophisticated representation of beliefs about ignorance and subjective expected utility representation, in an enriched framework, that assigns utility to the unknown while maintaining, in both instances, the flavor of reverse Bayesianism of Karni and Vierø (2013, 2014).
Keywords: D8; D81; D83; 330; Awareness; unawareness; ignorance; reverse Bayesianism